2022
DOI: 10.3389/fvets.2022.870735
|View full text |Cite
|
Sign up to set email alerts
|

Novel Single Nucleotide Polymorphisms (SNPs) and Genetic Features of the Prion Protein Gene (PRNP) in Quail (Coturnix japonica)

Abstract: Prion diseases are fatal infectious diseases caused by conformational changes of a prion protein (PrPSc) derived from a normal prion protein (PrPC). Prion diseases have been reported in several mammalian hosts but not in any birds, including the most popular poultry species, of which chickens showed some resistance to experimental prion infection. To identify the genetic polymorphisms in the quail prion protein gene (PRNP), polymerase chain reaction and DNA sequencing were performed with gene-specific primers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…At that time, its performance was better than previous state-of-the-art predictors. Since its publication, AMYCO implementation has been used to gain insights into prion evolution, especially the appearance and conservation of prion-protective or -enhancing mutations in different mammals [103][104][105][106] and birds [107]. It has also been used to identify prion disease-related somatic mutation in the prion gene from cancer patients [108] or to rationalize the effect of point mutations in the hnRNPDL gene on the onset of a rare type of muscular atrophy [109].…”
Section: Amyco: a Server For Prediction Of The Impact Of Mutations On...mentioning
confidence: 99%
“…At that time, its performance was better than previous state-of-the-art predictors. Since its publication, AMYCO implementation has been used to gain insights into prion evolution, especially the appearance and conservation of prion-protective or -enhancing mutations in different mammals [103][104][105][106] and birds [107]. It has also been used to identify prion disease-related somatic mutation in the prion gene from cancer patients [108] or to rationalize the effect of point mutations in the hnRNPDL gene on the onset of a rare type of muscular atrophy [109].…”
Section: Amyco: a Server For Prediction Of The Impact Of Mutations On...mentioning
confidence: 99%
“…Of them, c.163_180delAACCCAGGGTACCCCCAT is a hexapeptide deletion polymorphism in unit (U) 2 of the tandem repeat spanning U1 to U7 (32). Interestingly, a substantial number of polymorphisms, consisting of 33 SNPs in quails and 28 SNPs along with six insertion/deletion polymorphisms in pheasants, were identified within their PRNP gene (41,42). Moreover, when compared to chickens, the structure of the hexapeptide repeat region in both quails and pheasants remains highly conserved.…”
Section: Comparison Of Polymorphism Distributions Among Avian Speciesmentioning
confidence: 99%
“…In addition, when a substitution to incorporate a specific amino acid from chicken PrP occurred in the PrP sequence of domestic ducks, the amyloid propensity was observed to decrease, compared with that of wildtype duck (33). Furthermore, polymorphisms of the PRNP gene have been identified in many animals (10,31,32,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). However, no studies on PRNP polymorphisms in domestic ducks have yet been reported.…”
Section: Introductionmentioning
confidence: 99%